Do you really understand what you read? - Ahmad Nasaruddin, Sulaiman; Asiah, Kassim (2010)
Reading is an essential element in language learning. Second language learners may find reading a challenging task since language barriers exist in comprehension and information retention. At any education level, students are assessed on their reading comprehension ability. These evaluations and assessments come in many forms, such as multiple choice questions and short answers. Strategies like the skills to scan and skim salient information, identify main ideas, use contextual clues and make sense of references in texts are being exposed to students in order to equip them for the assessments. However, do students really understand what they read? Or are they just simply applying all the strategies acquired in answering comprehension questions? A study which involved 60 undergraduates taking reading course was carried out to address these questions. Findings indicate that students are able to apply the strategies effectively to some extent depending on the syntactical and lexical elements of the question formations. The study also illustrates that students may perform well in the test, but lack understanding in the text read. These assumptions elicit issues on the tasks and the assessments to be chosen that may be considered as effective in measuring the students' real reading performance.